Adaptive Finite Element Technique For Viscous Flow Analysis - Pramote Dechaumphai; Supatpong Sikkhabandit (ASEAN Journal on Science and Technology for Development, 2000)
Adaptive Finite Element Technique For Viscous Flow Analysis